Different perception of chronic constipation between patients and gastroenterologists. Issue 8 (25th March 2018) - Bellini, M.; Gambaccini, D.; Salvadori, S.; Bocchini, R.; Pucciani, F.; Bove, A.; Alduini, P.; Battaglia, E.; Bassotti, G.
Abstract: Background: There is a certain number of subjects that consider themselves to be constipated (self diagnosed constipation; SDC). The Rome Criteria separate FC from IBS‐C, but some SDC patients do not meet the Rome criteria (no Rome Constipation; NRC). Our aims were to evaluate the percentage of SDC subjects with a diagnosis of FC and IBS‐C and to compare demographic and clinical features, symptoms, and quality of life in the different SDC groups (FC, IBS‐C, NRC). Methods: During a 2‐month period, 934 patients and 980 accompanying persons (AP) were asked to complete a survey. The presence of FC or IBS‐C was assessed. SDC subjects were invited to record the stool consistency (Bristol scale) and to fill in the Constipation Severity Index (CSI), obstructed defecation syndrome (ODS) and patient assessment of constipation‐quality of life (PAC‐QoL). The use of laxatives and enemas was evaluated. Key Results: The probability of the ROME III criteria being present was higher in SDC compared with no‐SDC (OR 20.5). NRC was present in 13.5% of the SDC. In the patients' group the agreement between a diagnosis of Rome III and SDC was good (K 0.62), whereas in the AP it was moderate (K 0.56). NRC showed lower mean values of ODS, CSI and PAC‐QoL, higher Bristol scale and a lower use of laxatives and enemas compared to IBS‐C and FC. No differences were found between IBS‐C and FC. Conclusions and Inferences: The Rome III criteria identify subjects with a greater clinical impact, but separation of FC and IBS‐C does not seem justified. Abstract : IBS‐C, FC and No Rome Constipation: what's the difference?